Human Resources Development Strategy at the Tanjungpinang City Office of Women's Empowerment, Child Protection and Community Empowerment (DP3APM) - Satriadi, Satriadi; Iadhalia, Adhine; Khasanah, Fera Uswatun; Armelina, Gita; Purweny, Heni (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
Human Resources (HR) are the main driver of an organization's sustainability, therefore, a human resource development strategy is needed to create superior human resources and achieve organizational goals. The aim of this research is to determine the indicators used as measuring tools for human resources development strategies at the Tanjungpinang City Women's Empowerment, Child Protection and Community Empowerment Service (DP3APM), especially in the form of education, training, development, recruitment and system changes based on relevant literature regarding This and its effectiveness, in the implementation process, budget limitations and employee education levels are obstacles, especially training targets that require a fairly large budget. The research method used is a qualitative method with a descriptive approach, data was obtained through interviews and direct observation at the research location. The population in this study was 60 DP3APM employees and the sample was the DP3PAM Administration and Personnel Subdivision.